A study on estimate of Iodine Deficiency Disorders and adequacy of Iodized Salt Consumption in Begusarai district of Bihar, India - Kumar, Pragya; Agrawal, Neeraj; Ranjan, Alok; Lohani, Pallavi; Nirala, Santosh; Pandey, Sanjay; Singh, C M (Indian Journal of Community Health, 2019)
Background: Iodine Deficiency Disorder is major public health problem causing increased perinatal mortality, mental retardation and goiter and all these morbidities are preventable. Most effective and inexpensive mode to prevent IDD is consumption of iodized salt. Objectives: To estimate the proportion of households using adequately iodized salt in Begusarai district, to assess the knowledge of households on consumption and storage of salt and to estimate Total Goitre Rate (TGR). Material and Methods: Community- based cross sectional study carried out on 412 household from 30 cluster in Begusarai district using cluster sampling technique. Children (6-12 years) were examined clinically for goitre status and sample of household salt was collected for testing iodine content. Iodine content estimation was done both quantitatively by titration and qualitatively by MBI kit. Statistical analysis was performed using SPSS version 22. Result: The respondents were mainly female (92.8%) of mean age 34 years. Three- fifth (61.6%) participants used packaged crushed salt for cooking purpose, followed by packaged crystal (30.5%). Only 12.1 % of the respondents gave affirmative answer for presence of label and logo. Storage of salt in container with lid was 78.5%. The proportion of household using adequately iodized salt was 78%. The sensitivity MBI kit was 61% and the Total goiter rate was 9.3%. Conclusion: The Begusarai district falls in mild public health problem for IDD as TGR is more than 5% and even after many decades of effort towards achieving an adequately salt iodization of more than 90%, it is 79% only.